Intra parotid cystic lymphangioma masquerading as a neoplasm, a rare entity at unusual site - Nibedita Sahoo; Debahuti Mohapatra; Pranita Mohanty; Prateek Das; Debasmita Das (Wolters Kluwer Medknow Publications, 2019)
Cystic hygroma is an uncommon congenital malformation and usually present as an asymptomatic, painless, soft, fluctuant mass in infancy, and early childhood. The neck is the most common site followed by the face, tongue, and floor of the mouth. The primary site at parotid gland is extremely unusual, though it can secondarily involves parotid gland. Cystic lesion in parotid brings the other differentials of Warthin tumor, low-grade mucoepidermoid carcinomas, and lymphoepithelial cyst. Fine-needle aspiration cytology is not always diagnostic, and histopathology is the confirmatory. Primary parotid cystic lymphangioma is rare and even rarer in the adult age group. Herein, we report a case of primary parotid cystic hygroma in a 24-year-old male, which was misdiagnosed in cytology and later confirmed by histopathology.